Improvement of Gain Accuracy and CMRR of Low Power Instrumentation Amplifier Using High Gain Operational Amplifiers - Sahu, Rashmi; Konar, Maitraiyee; Kundu, Sudip (Micro and Nanosystems, 2020)
Background: Sensing of biomedical signals is crucial for monitoring of various health conditions. These signals have a very low amplitude (in μ V) and a small frequency range (< 500 Hz). In the presence of various common-mode interferences, biomedical signals are difficult to detect. Instrumentation amplifiers (INAs) are usually preferred to detect these signals due to their high commonmode rejection ratio (CMRR). Gain accuracy and CMRR are two important parameters associated with any INA. This article, therefore, focuses on the improvement of the gain accuracy and CMRR of a low power INA topology. Objective: The objective of this article is to achieve high gain accuracy and CMRR of low power INA by having high gain operational amplifiers (Op-Amps), which are the building blocks of the INAs. Methods: For the implementation of the Op-Amps and the INAs, the Cadence Virtuoso tool was used. All the designs and implementation were realized in 0.18 μ m CMOS technology. Results: Three different Op-Amp topologies namely single-stage differential Op-Amp, folded cascode Op-Amp, and multi-stage Op-Amp were implemented. Using these Op-Amp topologies separately, three Op-Amp-based INAs were realized and compared. The INA designed using the high gain multistage Op-Amp topology of low-frequency gain of 123.89 dB achieves a CMRR of 164.1 dB, with the INA’ s gain accuracy as good as 99% , which is the best when compared to the other two INAs realized using the other two Op-Amp topologies implemented. Conclusion: Using very high gain Op-Amps as the building blocks of the INA improves the gain accuracy of the INA and enhances the CMRR of the INA. The three Op-Amp-based INA designed with the multi-stage Op-Amps shows state-of-the-art characteristics as its gain accuracy is 99% and CMRR is as high as 164.1 dB. The power consumed by this INA is 29.25 μ W by operating on a power supply of ± 0.9V. This makes this INA highly suitable for low power measurement applications.
Keywords: folded cascode amplifier